The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jrh.12658
|View full text |Cite
|
Sign up to set email alerts
|

Trends in rural‐urban disparities among surgical specialties treating cancer, 2004‐2017

Abstract: Purpose We evaluated temporal trends in rural‐urban disparities of the surgeon supply among surgeons commonly treating patients with cancer. Methods We performed a retrospective observational study of county‐level workforce changes from 2004 to 2017 using the Area Health Resource File. We calculated physician density (providers/100,000 population) for each specialty by rural and urban counties using the 2003 Rural‐Urban Commuting Codes (RUCC), and evaluated percent changes in the rural‐urban disparity in physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A second population more likely to capitalize on a relaxation of state telemedicine restrictions are rural beneficiaries and those who live in counties with fewer physicians per capita. We believe these differences are partly driven by the lack of availability of specialty clinicians in the local community in rural areas and specifically the lack of availability of tertiary care centers . This likely explains why we saw greater use of out-of-state telemedicine for conditions such as cancer and conditions treated by uncommon specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second population more likely to capitalize on a relaxation of state telemedicine restrictions are rural beneficiaries and those who live in counties with fewer physicians per capita. We believe these differences are partly driven by the lack of availability of specialty clinicians in the local community in rural areas and specifically the lack of availability of tertiary care centers . This likely explains why we saw greater use of out-of-state telemedicine for conditions such as cancer and conditions treated by uncommon specialists.…”
Section: Discussionmentioning
confidence: 99%
“…We believe these differences are partly driven by the lack of availability of specialty clinicians in the local community in rural areas and specifically the lack of availability of tertiary care centers. 22 , 23 , 24 This likely explains why we saw greater use of out-of-state telemedicine for conditions such as cancer and conditions treated by uncommon specialists. As state licensure regulations change, it will be important to track telemedicine use among these populations to assess if use differentially falls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of cigarette smoking in rural Appalachian Ohio was 27% among men and 26% among women in 2019; in non-Appalachian metro areas of Ohio the prevalence of cigarette smoking was 23% among men and 21% among women [41]. These disparities in cigarette smoking, in combination with other factors including higher poverty rates and reduced access to specialized health care [42,43], contribute to cancer disparities for people living in rural and Appalachian regions of the United States [29][30][31][32]. With the stubbornly high prevalence of tobacco use in these regions, approaches that involve switching from a higher-risk to a lower-risk tobacco product, such as ONPs [11],…”
Section: Discussionmentioning
confidence: 99%
“…The loss of surgeons and surgical service lines may be a precursor to hospital closure. Studies show that surgeon supply has decreased in rural counties with rural‐urban disparities being most pronounced among general surgeons 23 . Another study found that annual reductions in the supply of general surgeons and surgical specialists led to rural hospital closures 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that surgeon supply has decreased in rural counties with rural-urban disparities being most pronounced among general surgeons. 23 Another study found that annual reductions in the supply of general surgeons and surgical specialists led to rural hospital closures. 24 The loss of these providers, and the subsequent loss of revenue from surgical procedures, may be a factor in rural hospital clo-sures in addition to the lack of Medicaid expansion that may protect against uncompensated care and improve revenue and margins.…”
Section: Discussionmentioning
confidence: 99%